C9orf72 Hexanucleotide Repeat Expansion and Guam Amyotrophic Lateral Sclerosis–Parkinsonism-Dementia Complex - Dombroski, Beth A. (2013)
IMPORTANCE: High-prevalence foci of amyotrophic lateral sclerosis (ALS) and parkinsonism-dementia complex (PDC) exist in Japanese on the Kii Peninsula of Japan and in the Chamorros of Guam. Clinical and neuropathologic similarities suggest that the disease in these 2 populations may be related. Recent findings showed that some of the Kii Peninsula ALS cases had pathogenic C9orf72 repeat expansions, a genotype that causes ALS in Western populations. OBJECTIVES: To perform genotyping among Guam residents to determine if the C9orf72 expanded repeat allele contributes to ALS-PDC in this population and to evaluate LRRK2 for mutations in the same population. Design and Setting Case-control series from neurodegenerative disease research programs on Guam that screened residents for ALS, PDC, and dementia. Participants Study participants included 24 with ALS and 22 with PDC and 43 older control subjects with normal cognition ascertained between 1956 and 2006. All but one participant were Chamorro, the indigenous people of Guam. A single individual of white race/ethnicity with ALS was ascertained on Guam during the study. Main Outcomes and Measures Participants were screened for C9orf72 hexanucleotide repeat length. Participants with repeat numbers in great excess of 30 were considered to have pathogenic repeat expansions. LRRK2 was screened for point mutations by DNA sequencing. Results We found a single individual with an expanded pathogenic hexanucleotide repeat. This individual of white race/ethnicity with ALS was living on Guam at the time of ascertainment but had been born in the United States. All Chamorro participants with ALS and PDC and control subjects had normal repeats, ranging from 2 to 17 copies. No pathogenic LRRK2 mutations were found. Conclusions and Relevance Unlike participants with ALS from the Kii Peninsula, C9orf72 expansions do not cause ALS-PDC in Chamorros. Likewise, LRRK2 mutations do not cause Guam ALS-PDC.